Nucleon-nucleon scattering within a multiple subtractive renormalization approach - Timóteo, V. S.; Frederico, T.; Delfino, A.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2011)
We present a methodology to renormalize the nucleon-nucleon interaction in momentum space, using a recursive multiple subtraction approach that prescinds from a cutoff regularization, to construct the kernel of the scattering equation. The subtracted scattering equation is solved with the next-leading-order and next-to-next-leading-order interactions. The results are presented for all partial waves up to j=2, fitted to low-energy experimental data. In this renormalization group invariant approach, the subtraction energy emerges as a renormalization scale and the momentum associated with it comes to be about the QCD scale (ΛQCD), irrespectively to the partial wave. © 2011 American Physical Society.